2010
DOI: 10.2527/jas.2009-2183
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of behavioral and physiological symptoms of preslaughter stress to beef longissimus muscle tenderness1

Abstract: Relationships between behavioral and physiological symptoms of preslaughter stress and LM Warner-Bratzler shear force (WBSF) were investigated using Bos taurus steers (n = 79) and heifers (n = 77). Measurements of heart rate, respiration rate, rectal temperature, and concentrations of serum cortisol and plasma epinephrine were used as indicators of stress associated with physical handling and chute restraint, whereas concentrations of cortisol, glucose, lactate, and creatine kinase in blood samples obtained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 27 publications
6
74
1
15
Order By: Relevance
“…Beef that has pH u > 6.0 after slaughtering indicates a change in the quality of meat. The meat has a dark red color (dark firm and dry/DFD) (Gruber et al, 2010), a high level of tenderness variation, and low palatability (Mach et al, 2008).…”
Section: Meat Phmentioning
confidence: 99%
“…Beef that has pH u > 6.0 after slaughtering indicates a change in the quality of meat. The meat has a dark red color (dark firm and dry/DFD) (Gruber et al, 2010), a high level of tenderness variation, and low palatability (Mach et al, 2008).…”
Section: Meat Phmentioning
confidence: 99%
“…GrUBer et al (2010) encontraram valores médios de 11,97 mMol/L para a concentração de lactato no período pós-abate em bovinos Angus, valores próximos aos encontrados no presente estudo, e concluíram que a maioria dos bovinos (70%) demonstram sintomas de estresse e aumento das concentrações sanguíneas de lactato quando submetidos ao manejo físico ou após serem transportados.…”
Section: Discussionunclassified
“…Segundo GrUBer et al (2010), bovinos com altas concentrações de lactato sanguíneo produzem carnes menos macias, com maior força de cisalhamento.…”
Section: Introductionunclassified
“…Physiological measures can easily show differences between low-stress and high-stress handling (Edwards et al 2010;Brandt and Aaslying 2015). At the slaughter plant, when pigs and cattle were moved with electric prods or jammed in the race that leads to the stunner, lactate and glucose concentrations are higher (Edwards et al 2010;Gruber et al 2010). Edwards et al (2010) measured blood lactate in pigs and Gruber et al (2010) measured plasma lactate and plasma glucose in cattle.…”
Section: Use Of Physiological Measures To Evaluate Handling Practicesmentioning
confidence: 99%
“…At the slaughter plant, when pigs and cattle were moved with electric prods or jammed in the race that leads to the stunner, lactate and glucose concentrations are higher (Edwards et al 2010;Gruber et al 2010). Edwards et al (2010) measured blood lactate in pigs and Gruber et al (2010) measured plasma lactate and plasma glucose in cattle. Benjamin et al (2001) found that both glucose and blood lactate were doubled or tripled immediately after aggressive handling with multiple shocks from an electric prod, compared with calm handling with no prods.…”
Section: Use Of Physiological Measures To Evaluate Handling Practicesmentioning
confidence: 99%